Eschatological Features in Malachi 4:1-6 - Henry Tembo (Jurnal Koinonia, 2022)
This article exegetes the eschatology of Malachi 4:1-6. Most studies mention the subject in passing leaving the eschatology of the text opaque. The issue compounds when studies apply incomprehensive methodologies. The impact of this exegetical hole shows up in divergent views of fulfilment. A major area of interest among studies of prophetic texts. The article utilizes a multifaceted prophetic exegesis. The method incorporates various aspects of text analysis to define the eschatology within the text. It touches historical and literary aspects. It analyses issues related to typology. It’s focus leads the exegete to give due attention to fulfilment of prophetic texts. It uncovers the eschatological substructure imbedded in the text. The approach demonstrates that Malachi 4:1-6 contains eschatological features in the immediate context. These features transcend the immediate context when the person of John the Baptist and Jesus enter the biblical narrative. Beyond these two biblical figures. The study considers eschatology in light of the NT. At the end, the article summarizes and key findings